A Multicriteria Decision Model for Supplier Selection in a Food Industry Based on FITradeoff Method. (19th October 2017) - Frej, Eduarda Asfora; Roselli, Lucia Reis Peixoto; Araújo de Almeida, Jônatas; de Almeida, Adiel Teixeira
Abstract : This article puts forward a decision model for solving a supplier selection problem in a food industry by considering multiple objectives that influence the decision-making process. In times of increasing competitiveness, companies strive hard to improve their profitability, and selection of supply sources may help if an appropriate decision is made through a well-structured decision-making process. Preference modeling is conducted in a flexible and interactive elicitation manner with the decision-maker (DM), aided by FITradeoff method. Partial information is gathered about the DM's preferences in such a way that less effort is spent on finding a final solution for the problem.